Reconstructing the Indonesian Legal System through the Lens of Maṣlaḥah Mursalah - Nasrullah; Moh Najib; Uu Nurul Huda; Enceng Arif Faizal (Al-Manahij: Jurnal Kajian Hukum Islam)
This article examines the construction of the Indonesian legal system through the theoretical lens of maṣlaḥah mursalah, an Islamic legal principle centered on public interest and benefit. The study contributes to the expansion of Islamic legal scholarship within the realm of legal politics in Indonesia. Employing a normative legal research method, it integrates conceptual, historical, and statutory approaches to examine the relevance and application of maṣlaḥah mursalah in the national legal framework. The findings indicate that maṣlaḥah mursalah can serve as a foundational legal theory for constructing a just legal system, especially one that aligns with societal needs and promotes the common good. The Indonesian legal system's development, when viewed through the prism of maṣlaḥah mursalah, reveals two key dimensions: first, the legal construction rooted in the Pancasila-based system as constitutionally mandated by the 1945 Constitution, and second, the partial institutionalization of Islamic law within the national legal order. This dual structure reflects Indonesia's efforts to harmonize religious values with national legal development, offering a model for integrating Islamic jurisprudence with modern state law.